Las atribuciones del notario en materia de familia, mujer, niñez y adolescencia - Sarango Abril, Nayelli Rashell (2026)
The research addresses the analysis of the attributions of the notary in the area of family, women, children and adolescence law in Ecuador, from the evolution of notarial law from colonial times to the modern reforms of 2016. The central problem focuses on the ambiguity of Article 234.1 of the Organic Code of the Judicial Function, which mentions shared competences between judges and notaries without clearly delimiting their scope. This indeterminacy generates uncertainty as to when notaries can act autonomously and when a judicial process is required. The main objective of the research is to identify and clarify such notarial powers in sensitive matters involving fundamental rights. The methodology used was qualitative, of a legal-dogmatic type, with a descriptive design and interpretative approach, using dogmatic and hermeneutic methods, in addition to documentary analysis techniques. As a result, it became evident that notaries can intervene independently only in non-contentious acts expressly authorized by law, such as divorces by mutual agreement without minor children and the termination of de facto unions, provided that the rights of vulnerable persons are not compromised. On the other hand, in cases where there is a conflict of interest, involvement of minors or persons with disabilities, or where judicial control is required, the competence falls exclusively on specialized judges. It is concluded that the current regulatory ambiguity may jeopardize the principle of legal certainty and effective judicial protection, being essential a precise regulatory delimitation to ensure the correct articulation between the notarial and jurisdictional function.